2011
DOI: 10.1007/s12275-011-1260-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of resistomycin, as an anticancer compound isolated and characterized from Streptomyces aurantiacus AAA5

Abstract: A new actinomycete strain, isolated from humus soils in the Western Ghats, was found to be an efficient pigment producer. The strain, designated AAA5, was identified as a putative Streptomyces aurantiacus strain based on cultural properties, morphology, carbon source utilization, and analysis of the 16S rRNA gene. The strain produced a reddish-brown pigmented compound during the secondary metabolites phase. A yellow compound was derived from the extracted pigment and was identified as the quinone-related antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 23 publications
1
41
0
1
Order By: Relevance
“…In the present study, the bioassayguided separation of an extract of the cultured media of the actinomycete strain CKK1172 led to the isolation of resistomycin (1). The antimicrobial and cytotoxic activities of 1 were described previously [8], while we herein reported the TRAIL resistanceovercoming activity of 1 at 2 µM in AGS cells for the first time, thereby suggesting their possible use in combination with TRAIL against AGS cells.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…In the present study, the bioassayguided separation of an extract of the cultured media of the actinomycete strain CKK1172 led to the isolation of resistomycin (1). The antimicrobial and cytotoxic activities of 1 were described previously [8], while we herein reported the TRAIL resistanceovercoming activity of 1 at 2 µM in AGS cells for the first time, thereby suggesting their possible use in combination with TRAIL against AGS cells.…”
supporting
confidence: 58%
“…A large-scale culture using liquid Waksman media (11.2 L) with shaking at 28 °C for 5 days was separated into a supernatant and mycelia by centrifugation. The EtOAc-soluble fraction of the supernatant of the culture was subjected to silica gel and ODS column chromatography, followed by preparative ODS HPLC to provide resistomycin (1, ESIMS m/z 377 [M+H] + ) (Figure 1), which was identified by comparisons with published spectral data [7,8]. The occurrence of resistomycin (1) was previously reported from culture broths of several kinds of actinomycetes [7][8][9][10].…”
mentioning
confidence: 87%
“…The identity of each compound was verified by (−)-FTICR MS and analysis of NMR spectra (Figure S1). All three of these compounds have reported cytotoxicity against mammalian cells (Martin et al, 2002; Gorajana et al, 2007; Vijayabharathi et al, 2011). Furthermore, resistomycin has recently been shown to bind DNA by fluorescence competition experiments and circular dichroism studies (Vijayabharathi et al, 2012), and to prevent transcription by inhibition of RNA polymerase (Arora, 1985).…”
Section: Resultsmentioning
confidence: 99%
“…In a similar study, Vijayabharathi et al [53] reported that Sterptomyces strain, isolated from humus soils in the Western Ghats, has an anticancer activity against HepG2 (hepatic carcinoma) and HeLa (cervical carcinoma) in vitro. Secondary metabolites from actinomycetes, Figure 6.…”
Section: Cell Immobilizationmentioning
confidence: 87%